2015
DOI: 10.1007/978-3-319-25479-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Securing the Information Infrastructure for EV Charging

Abstract: We consider the functional and security requirements for the information exchanges in the infrastructure for EV charging being trialled in the Netherlands, which includes support for congestion management using the smart charging protocol OSCP. We note that current solutions do not provide true end-to-end security, even if all communication links are secured (for instance with TLS), as some data is forwarded between multiple parties. We argue that securing the data itself rather than just securing the communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, since the official did not set up a special database for electric vehicle fires, we only counted 122 electric vehicle accidents with cause reports from major news reports. In these 122 accidents, the frequency of accidents caused by various risk factors was obtained by screening with each major risk factor as the keyword, and the accident probability caused by each risk factor was obtained by using Equation (13). As shown in Table A2, the risk probability was homogenized to obtain the homogenized probability, which is used as the node conditional probability for Bayesian network calculation.…”
Section: Bayesian Network Structure and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the official did not set up a special database for electric vehicle fires, we only counted 122 electric vehicle accidents with cause reports from major news reports. In these 122 accidents, the frequency of accidents caused by various risk factors was obtained by screening with each major risk factor as the keyword, and the accident probability caused by each risk factor was obtained by using Equation (13). As shown in Table A2, the risk probability was homogenized to obtain the homogenized probability, which is used as the node conditional probability for Bayesian network calculation.…”
Section: Bayesian Network Structure and Data Processingmentioning
confidence: 99%
“…For the charging safety of electric vehicles, the German ZSW Research Center [12] showed through the analysis of experimental data that the lithium dendrite formed in the battery during the charging process was the primary cause of thermal runaway of electric vehicle batteries. Van den Broek and Fabian et al [13] believe that building the communication connection between electric vehicle charging stations can better improve the charging safety of electric vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…At public charge points drivers are authenticated through the use of an RFID card. As already mentioned in [3], every customer is identified using only the card's UID that is transmitted plaintext through the air. We will refer to this mechanism as the weak UID method.…”
Section: Using Uids For Authentication Of the Ev Driver Or Evmentioning
confidence: 99%
“…• Finally, there are Industry Consortia that cut across roles to bring parties together in an effort to improve collaboration. Examples are the NKL organization 3 , ElaadNL 4 , and the Open Charge Alliance 5 . One major activity these consortia undertake is the standardization and promotion of protocols.…”
Section: Introductionmentioning
confidence: 99%